Fumarate Hydratase-deficient Renal Cell Carcinoma Is Strongly Correlated With Fumarate Hydratase Mutation and Hereditary Leiomyomatosis and Renal Cell Carcinoma Syndrome - Trpkov, Kiril; Hes, Ondrej; Agaimy, Abbas; Bonert, Michael; Martinek, Petr; Magi-Galluzzi, Cristina; Kristiansen, Glen; Lüders, Christine; Nesi, Gabriella; Compérat, Eva; Sibony, Mathilde; Berney, Daniel M; et al. (The American journal of surgical pathology, 2016)
Hereditary leiomyomatosis and renal cell carcinoma syndrome-associated renal cell carcinomas (RCC) are difficult to diagnose prospectively. We used immunohistochemistry (IHC) to identify fumarate hydratase (FH)-deficient tumors (defined as FH negative, 2-succinocysteine [2SC] positive) in cases diagnosed as "unclassified RCC, high grade or with papillary pattern," or "papillary RCC type 2," from multiple institutions. A total of 124 tumors (from 118 patients) were evaluated by IHC for FH and 2SC. An FH deficiency was found in 24/124 (19%) cases. An indeterminate result (only 1 marker abnormal) was found in 27/124 (22%) cases. In a tissue microarray of 776 RCCs of different types, only 2 (0.5%) tumors, initially considered papillary type 2, were FH deficient. FH mutations were found in 19/21 FH-deficient tumors (with confirmed germline mutations in 9 of 9 tumors in which germline status could be assessed) and in 1/26 FH-indeterminate tumors identified by IHC. No FH mutations were found in 2/21 FH-deficient RCCs, 25/26 FH-indeterminate RCCs, and 10/10 RCCs demonstrating FH expression by IHC. Patients with FH-deficient RCC had a median age of 44 years (range, 21 to 65 y). Average tumor size was 8.2 cm (range, 0.9 to 18 cm). FH-deficient RCCs were characterized by at least focal macronucleoli and demonstrated 2 or more growth patterns in 93% cases. Papillary was the most common (74%) and dominant (59%) pattern, whereas other common patterns included: solid (44%), tubulocystic (41%), cribriform (41%), and cystic (33%). At presentation, 57% were stage ≥pT3, 52% had positive nodes, and 19% had distant metastases. After a mean follow-up of 27 months (range, 1 to 114 mo), 39% of patients were dead of disease, and 26% had disease progression. We conclude that FH and 2SC are useful IHC ancillary tools, which allow recognition of FH-deficient RCC.
Keywords: Male; Fumarate Hydratase; Psychomotor Disorders; lidé středního věku; Cysteine; nádory dělohy; svalová hypotonie; Carcinoma, Renal Cell; Muscle Hypotonia; vrozené poruchy metabolismu; Humans; Immunohistochemistry; Skin Neoplasms; Uterine Neoplasms; dědičné nádorové syndromy; karcinom z renálních buněk; Middle Aged; senioři; Leiomyomatosis; Kidney Neoplasms; mužské pohlaví; Female; Neoplastic Syndromes, Hereditary; leiomyomatóza; zárodečné mutace; Aged; ženské pohlaví; nádory kůže; čipová analýza tkání; Germ-Line Mutation; mladý dospělý; Adult; Metabolism, Inborn Errors; Young Adult; psychomotorické poruchy; fumarasa; imunohistochemie; Tissue Array Analysis; dospělí; lidé; nádory ledvin; cystein